An 8.5 m long ammonite drag mark from the Upper Jurassic Solnhofen Lithographic Limestones, Germany. - Dean R Lomax; Peter L Falkingham; Günter Schweigert; Alejandro P Jiménez (PLoS ONE, 2017)
Trackways and tracemakers preserved together in the fossil record are rare. However, the co-occurrence of a drag mark, together with the dead animal that produced it, is exceptional. Here, we describe an 8.5 m long ammonite drag mark complete with the preserved ammonite shell (Subplanites rueppellianus) at its end. Previously recorded examples preserve ammonites with drag marks of < 1 m. The specimen was recovered from a quarry near Solnhofen, southern Germany. The drag mark consists of continuous parallel ridges and furrows produced by the ribs of the ammonite shell as it drifted just above the sediment surface, and does not reflect behaviour of the living animal.